2006
DOI: 10.1038/sj.onc.1209594
|View full text |Cite
|
Sign up to set email alerts
|

Succinate dehydrogenase and fumarate hydratase: linking mitochondrial dysfunction and cancer

Abstract: The phenomenon of enhanced glycolysis in tumours has been acknowledged for decades, but biochemical evidence to explain it is only just beginning to emerge. A significant hint as to the triggers and advantages of enhanced glycolysis in tumours was supplied by the recent discovery that succinate dehydrogenase (SDH) and fumarate hydratase (FH) are tumour suppressors and which associated, for the first time, mitochondrial enzymes and their dysfunction with tumorigenesis. Further steps forward showed that the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
461
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(482 citation statements)
references
References 62 publications
8
461
1
12
Order By: Relevance
“…While the original publication of MTA has mainly focused on its testing and validation in a known collection of gene knockouts in microorganisms, it already showed that MTA correctly identifies fumarate hydratase as a gene whose knockdown may cause the metabolic transformations observed in HLRCC (Kiuru et al , 2002; King et al , 2006). We now tested and validated that MTA successfully identifies the knockdown of succinate dehydrogenase (SDH) as a likely cause of the metabolic alterations observed in hereditary paraganglioma (Frezza et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…While the original publication of MTA has mainly focused on its testing and validation in a known collection of gene knockouts in microorganisms, it already showed that MTA correctly identifies fumarate hydratase as a gene whose knockdown may cause the metabolic transformations observed in HLRCC (Kiuru et al , 2002; King et al , 2006). We now tested and validated that MTA successfully identifies the knockdown of succinate dehydrogenase (SDH) as a likely cause of the metabolic alterations observed in hereditary paraganglioma (Frezza et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…34 The link between the loss of mitochondrial tumor suppressors and pseudo-hypoxia was indicated by several studies showing that SDH subunit mutations were linked with HIF-1 activation in highly vascularized tumors such as paragangliomas and pheochromocytomas. 35 Of note, microarray analysis of these SDH subunit-deficient tumors (including SDHD) revealed an HIF signature identical to that of a group of von Hippel-Lindau (VHL)-deficient tumors. 28 The VHL tumor suppressor is a key mediator of HIF activity, mediating ubiquitination and subsequent proteasome-mediated degradation of HIF-1a following its hydroxylation by HIF prolyl hydroxylase domain proteins (PHD1, 2 or 3) in normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Warburg averred that an irreversible injury to respiration had to occur in order to trigger the progressive striving of cells that had succeeded to engage in lactic fermentation to fulfill their energy needs, leading ultimately to the formation of a tumor (Warburg, 1956a). Mutations in mitochondrial DNA (Bonora et al, 2006), and defective mitochondrial lipid content and structure (Kiebish et al, 2008), were found to squelch respiration in some tumors, while malfunction of some Krebs cycle enzymes also contributes to apoptosis resistance and aerobic glycolysis (King et al, 2006). This suggests that mitochondrial defects may have a role in certain cancers.…”
Section: Perspectivesmentioning
confidence: 99%